2021
DOI: 10.1002/app.50722
|View full text |Cite
|
Sign up to set email alerts
|

Effects of molecular weight and molecular weight distribution on creep properties of polypropylene homopolymer

Abstract: The molecular weights of the industrial‐grade isotactic polypropylene (i‐PP) homopolymers samples were determined by the melt‐state rheological method and effects of molecular weight and molecular weight distribution on solid and melt state creep properties were investigated in detail. The melt‐state creep test results showed that the creep resistance of the samples increased by Mw due to the increased chain entanglements, while variations in the polydispersity index (PDI) values did not cause a considerable c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
(58 reference statements)
1
9
0
Order By: Relevance
“…The M n and M w of PP and PP-g-MAH are provided by the manufacturer. Kurt and Kasgoz [48] have experimentally measured the molecular weight of PP, which is the same material used in this study, using melt rheology, and reported that the molecular weight agreed with that provided by the manufacturer. Detailed characterization of grafted polymer is beyond our current research scope; therefore, we accept and report the manufacturer's value of PP-g-MAH molecular weight without further verification.…”
Section: Methodssupporting
confidence: 70%
“…The M n and M w of PP and PP-g-MAH are provided by the manufacturer. Kurt and Kasgoz [48] have experimentally measured the molecular weight of PP, which is the same material used in this study, using melt rheology, and reported that the molecular weight agreed with that provided by the manufacturer. Detailed characterization of grafted polymer is beyond our current research scope; therefore, we accept and report the manufacturer's value of PP-g-MAH molecular weight without further verification.…”
Section: Methodssupporting
confidence: 70%
“…In Figure 5 , the effect of this complex of radicals O-O-AsH-TiCl 4 -MgCl 2 is shown on the beginning of the degradation of PP, which consists of the abstraction of hydrogen in the PP-virgin, generating a stable tertiary radical, which, when reacting with a molecule O 2 , will produce a Peroxy-PP-virgin radical, which extracts hydrogen from a neighboring virgin-PP chain, thereby forming the virgin-PP-Hydroperoxide. The latter, after a homolytic rupture, will give rise to the Alkoxy-PP-Virgin radical [ 53 , 54 , 55 , 56 ]. The radical complex of O-O-ash-tiCl 4 -MgCl 2, after the abstraction of hydrogen, forms the peroxy complex H-O-O-AsH-TiCl 4 -MgCl 2 that, by hemolysis, forms the radical O-AsH-TiCl 4 -MgCl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to apply the theoretical and computational methods, the creep and recovery responses should be within the linear viscoelastic regime. The linear viscoelastic creep and recovery responses of polypropylene composites have been experimentally studied in the past (Wang et al 2018;Kurt and Kasgoz 2021;Wu et al 2019;Lee et al 2004;Homkhiew et al 2013;Rosa et al 2018). However, the experimental studies vary on the testing methods, the equipment used, and the testing conditions.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Using the universal testing machines, uniaxial tension (Wu et al 2019;Lee et al 2004;Zhai et al 2018;Houshyar et al 2005;Drozdova et al 2009) and flexural (Militký and Jabbar 2015;Tiwari et al 2021) tests are made to study creep of polypropylene composites. Nano-indentation tests (Rosa et al 2018;Dian et al 2020), a dynamic oscillatory rheometer (Kurt and Kasgoz 2021) and a dynamic mechanical analyser (Wang et al 2018;Houshyar et al 2005) are used to study the effects of chemical modification on the mechanical performance of polypropylene. Similarly, the creep and recovery behaviours of the polypropylene composites are studied at different temperatures (Wang et al 2018;Banik et al 2007;Militký and Jabbar 2015).…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation